2022
DOI: 10.1155/2022/1052699
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Ferroptosis in Adiposity-Based Chronic Disease (ABCD)

Abstract: Ferroptosis is a multistep regulated cell death process induced by iron accumulation and lipid peroxidation. Classical GPX4-dependent pathway and GPX4-independent pathways can independently and synergistically inhibit ferroptosis and jointly maintain the oxidative balance of the body. WHO defines obesity as “a condition of abnormal or excessive fat accumulation in adipose tissue, to the extent that health may be impaired,” and obesity is also defined as an adiposity-based chronic disease (ABCD). Obesity is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…This review summarizes the characteristics of iron metabolism in humans, the association between obesity and ferroptosis, and the neuroimmune regulation associated with obesity and ferroptosis. While many of these mechanisms are still unknown, there is growing evidence that ferroptosis plays a key role in obesity and its complications, including type II diabetes, hypertension, nonalcoholic steatohepatitis, atherosclerosis, and obese cardiomyopathy ( 171 ). Moreover, ferroptosis may not only play a direct role in AT, but also indirectly promote the development of obesity through the inflammatory response and insulin resistance caused by liver autonomic and immunomodulatory disorders( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review summarizes the characteristics of iron metabolism in humans, the association between obesity and ferroptosis, and the neuroimmune regulation associated with obesity and ferroptosis. While many of these mechanisms are still unknown, there is growing evidence that ferroptosis plays a key role in obesity and its complications, including type II diabetes, hypertension, nonalcoholic steatohepatitis, atherosclerosis, and obese cardiomyopathy ( 171 ). Moreover, ferroptosis may not only play a direct role in AT, but also indirectly promote the development of obesity through the inflammatory response and insulin resistance caused by liver autonomic and immunomodulatory disorders( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since ferroptosis was associated with lipid peroxidation, the dynamic change of lipid peroxidation is also involved in the development of obesity-related cardiomyopathy. Palmitic acid was found to inhibit the protein expression levels of GPX4 in a dose-and time-dependent manner and was restored by different ferroptosis inhibitors in vitro study (57). A recent study revealed that obese adipose tissue macrophages (ATMs) derived exosomes resulted in ferroptosis via glutathione synthesis disorder by targeting SLC7A11 in obesity-induced cardiac injury (58).…”
Section: Heart Failurementioning
confidence: 99%
“…In recent years, the relationship between iron and PNI has attracted increasing attention. In normal conditions, the system xc --GSH-GPX4 axis is responsible for the extracellular transport of cystine and the intracellular transport of glutamat [103]. A microenvironment is established upon nerve injury, which consists of axons, SCs, blood vessels, inflammatory factors and cells, extracellular matrix, and connective tissue [104].…”
Section: Ferroptosis and Peripheral Nerve Injurymentioning
confidence: 99%